TURATH: Islamic Architectural Heritage 2021 - Mohd Nawawi, Norwina; Asif, Nayeem; Denan, Zuraini; Hamat, Sufian; Aripin, Srazali; Shaharil, Muhammad Ihsan; Ishak, Izzatul Athirah; Md Faris, Nur Allysa Sara; Asmawi, Nur Imanisa; Roslaimi, Nur Amylia; Siddiqua, Rahnoma; Adlan, Nur Farahadlin; et al. (Department of Architecture, Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2021)
The publication is the combined product of an academic exercise in research and measuring the three historic masjids of the Gombak river, i.e. Masjid Sg Chin Chin, Masjid Lama Batu 6 and Masjid Lama Setapak by the graduating students of the IIUM Bachelor of Science in Architectural Studies programme. The research aims to record the history of the three masjids of their origin, their architectural build form, and materiality, as well as the culture of the community that sustains them. The qualitative research method was employed. Literature review, measured drawings, observation, interview, and comparison work were explored within the stipulated time. The significance of this research exercise includes the written and visual records of the three masjids that provide the students with learning experience and appreciation of heritage as their legacy for the future..